Implications of Leadership Style and Persuasive Communication on Performance Mediated by Employee Work Motivation - Irawanto; Hayati M; Semuel Risal (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to describe and analyze the implications of leadership style and persuasive communication on performance and motivation as mediation at the Agency for Personnel and Human Resources Development of East Barito Regency. This research was conducted quantitatively with an explanatory research approach. Sampling technique with the total sampling method. The analysis uses the Partial Least Square (PLS) method. The results showed that leadership style had a positive and significant effect on performance, leadership style had a positive and significant effect on motivation, persuasive communication had a positive and significant effect on performance, persuasive communication had no direct effect on motivation, then the influence of leadership style had no significant effect on performance through motivation, and persuasive communication has no significant effect on performance through motivation.